SAT0133 Management of Cardiovascular Risk Factors in Rheumatoid and Psoriatic Arthritis: The Australian Rheumatology Association Database (ARAD) Heart Health Survey. (15th July 2016) - Sinnathurai, P.; Capon, A.; Buchbinder, R.; Chand, V.; Henderson, L.; Lassere, M.; March, L.
Abstract : Background: Chronic inflammatory arthritis is associated with increased cardiovascular (CV) morbidity and mortality [1]. Furthermore, obesity is associated with a reduced chance of achieving low or minimal disease activity in rheumatoid arthritis (RA) and psoriatic arthritis (PsA) [2, 3]. EULAR guidelines recommend that patients with chronic inflammatory arthritis should receive screening and management for traditional CV risk factors [4]. Previous analysis showed that diabetes mellitus (DM) and high cholesterol were more common in patients with PsA than RA [5]. Objectives: To describe and compare current treatment patterns for CV risk factors in patients with RA and PsA in ARAD. Methods: ARAD is a voluntary national registry. Participants with inflammatory arthritis complete questionnaires every 6 -12 months in online or paper format. An additional Heart Health Survey was sent to online participants, including questions about pharmacological management of CV risk factors, dietary modification and physical activity. Results from the survey were linked with ARAD. Results: Out of 1973 online ARAD participants, 1254 (64%) responded to the Heart Health Survey. Unlike earlier analysis of the whole ARAD cohort, there were no significant differences in the prevalence of CV risk factors between the RA and PsA responders. Pharmacological or dietary management was utilised by all patients with DM. Most patients with hypertension received pharmacological treatment (RA 93%, PsA 94%). The majority of patients with hypercholesterolaemia also received pharmacological management (RA 69%, PsA 73%). However, utilisation of lifestyle modification for management of obesity was low. In obese patients, only 34% had made any dietary change for their health. 12% of obese patients with RA and 8% of obese patients with PsA had attended an exercise program. 63% of RA and 61% of PsA patients who were obese reported being physically inactive; undertaking less than 30 minutes of moderate physical activity on 3 or more days of the week. In obese patients, 79% with RA and 62% with PsA reported that their arthritis limited their ability to engage in physical activity. Conclusions: CV risk factors are common in this Australian cohort. Management of CV risk factors was similar between patients with RA and PsA. The majority of patients receive pharmacological management. However, lifestyle modifications appear to be underutilised in the management of obesity. Arthritis is reported as the main factor limiting respondents' physical activity. References: Ogdie A, et al. Ann Rheum Dis 2015;74(2):326–32. Eder L, et al. Ann Rheum Dis 2015;74(5):813–17. Sandberg ME, et al. Ann Rheum Dis 2014;73(11):2029–33. Peters MJL, et al. Ann Rheum Dis 2010;69(2):325–31. Internal Medicine Journal 2015;45(S2):1–46. Acknowledgement: The authors gratefully acknowledge Joan McPhee for her assistance with this project. Disclosure of Interest: None declared